Effects of mean stress on the durability assessment for an automobile crankshaft using Markov Chain Modelling Technique / S.S. K.Singh and S. Abdullah - K.Singh, S.S.; Abdullah, S. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
this paper presents the mean stress effect on durability assessment in terms of fatigue life prognosis under random loading using markov chain technique.durability assessment proposes the use of an embedded markov process by incorporating loading data samples to artificially generate a series of loadinghistory to predict the fatigue life cycle of the automobile crankshaft. themarkov process is continuously updated in order to minimize the loading data point for fatigue life prediction. the accuracy of the durability assessment ismodelled using the finite element analysis and Validated through statisticalcorrelation properties based on the random loading, material and design ofthe component. the durability assessment using the markov chain modellingtechnique provided a statistical accuracy between 95 - 97% with a meansquared error of less than 2% compared to sampling data. therefore, the useof a non-deterministic method of markov chain model provides a basis for thedevelopment of an accurate and efficient durability assessment between thestochastic model and practice of the deterministic method.